2015
DOI: 10.1177/1352458515576984
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence of increased susceptibility to varicella-zoster virus reactivation or reinfection in natalizumab-treated patients with multiple sclerosis

Abstract: Background: Serious adverse drug reactions of disease-modifying drugs in multiple sclerosis (MS) therapy may include enhanced susceptibility to reactivation of neurotropic herpes viruses like varicella-zoster virus (VZV) and the John Cunningham (JC) polyomavirus. Objective: Because symptomatic reactivation of these viruses are rare events, we determined the incidence of rises in anti-VZV IgG antibody levels as a potential marker for enhanced susceptibility to subclinical and symptomatic reactivation of neurotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Mild or moderate herpes zoster infections were reported in 2 of 47 patients (4%) treated with natalizumab. Previous reports have also found a slightly higher rate of herpes infection in natalizumab-treated patients compared with placebo-treated patients or healthy controls (Biogen, 2015;Fine et al, 2013;Kohlmann et al, 2015). However, the frequency of herpes infections does not appear to increase with longer duration of therapy, and the postmarketing reporting rate for herpes infections is consistent with the known safety profile for natalizumab.…”
Section: Discussionsupporting
confidence: 73%
“…Mild or moderate herpes zoster infections were reported in 2 of 47 patients (4%) treated with natalizumab. Previous reports have also found a slightly higher rate of herpes infection in natalizumab-treated patients compared with placebo-treated patients or healthy controls (Biogen, 2015;Fine et al, 2013;Kohlmann et al, 2015). However, the frequency of herpes infections does not appear to increase with longer duration of therapy, and the postmarketing reporting rate for herpes infections is consistent with the known safety profile for natalizumab.…”
Section: Discussionsupporting
confidence: 73%
“…This may result in less immunity in the upper gastrointestinal tract and as a consequence a higher risk to get a primary infection with the JCV. In addition Kohlmann et al [23] found an extremely high incidence of rising anti-VZV immunoglobulin G levels in natalizumab-treated MS patients in contrast to age-and gender-matched healthy blood donors and to HIV-infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is not totally excluded that this is (partly) caused by patients who were already infected (i.e. In addition Kohlmann et al [23] found an extremely high incidence of rising anti-VZV immunoglobulin G levels in natalizumab-treated MS patients in contrast to age-and gender-matched healthy blood donors and to HIV-infected patients. Recently, the results of some small studies suggested that patients can have viraemia without anti-JCV antibodies [5][6][7] more often than initially described by Rudick et al [19], who concluded that this was a rare condition.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, vaccination is performed in people who are seronegative for VZV (Singer 2013 ). However, increased rates of VZV/HZ infections have also been reported in MS patients receiving other immunosuppressive drugs, including the anti-integrin VLA-4 monoclonal antibody natalizumab, which blocks activated T cell migration into the CNS (Kohlmann et al 2015 ), and the anti-CD52 monoclonal antibody alemtuzumab, a T cell- and B cell-depleting antibody (Venkatachalapathy et al 2007 ). It appears in fact that the reporting of VZV infections in the post-marketing setting is disproportionate for fingolimod compared to the other disease-modifying treatments, and that the real frequencies may be comparable (Arvin et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%